Self-assembly of magnesium-seamed hexameric pyrogallol[4]arene nanocapsules. Issue 31 (21st March 2017) - Zhang, Chen; Patil, Rahul S.; Li, Tao; Barnes, Charles L.; Atwood, Jerry L.
Abstract : The magnesium-seamed hexameric pyrogallol[4]arene nanocapsule and its cocrystallization with pyridine molecules are presented. Abstract : The solvothermal synthesis of a metal-seamed hexameric nanocapsule from pyrogallol[4]arenes and magnesium is reported. The unique non-toxic and biocompatible nature of divalent magnesium cations in addition to the large inherent cavities make these nanocapsules promising for potential application in biomedicine. In addition, we show that these nanocapsules can form cocrystals with pyridine molecules through hydrogen bonding, which sheds light to cocrystallization of supramolecular nanocapsules with small pharmaceutics.